2002
DOI: 10.1051/0004-6361:20011580
|View full text |Cite
|
Sign up to set email alerts
|

Mineral formation in stellar winds

Abstract: Abstract. S stars are transition objects at the top of the AGB between M-and C-stars. The third dredge-up in thermally pulsating AGB-stars transports freshly synthesised carbon from the He burning zone into the stellar atmosphere. If the carbon and oxygen abundance are about equal the star is classified as being of spectral type S. Stars at the top of the AGB are subject to large mass-loss caused by a strong stellar wind. At some distance from the star the temperature of the gas drops below the condensation te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(109 citation statements)
references
References 46 publications
1
108
0
Order By: Relevance
“…We may say that these two C/O values bracket the transition region between the O-dominated and the C-dominated chemistry. As discussed by Ferrarotti & Gail (2002) the abrupt changes in the chemical equilibria at C/O ≈ 0.93 and C/O ≈ 1.0 respectively correspond to the critical values of the carbon abundance…”
Section: Varying C-n-o Mixturesmentioning
confidence: 86%
See 1 more Smart Citation
“…We may say that these two C/O values bracket the transition region between the O-dominated and the C-dominated chemistry. As discussed by Ferrarotti & Gail (2002) the abrupt changes in the chemical equilibria at C/O ≈ 0.93 and C/O ≈ 1.0 respectively correspond to the critical values of the carbon abundance…”
Section: Varying C-n-o Mixturesmentioning
confidence: 86%
“…C, O, and to a less extent Si. Following Ferrarotti & Gail (2002) for temperatures T < ∼ 1500 K, at which dust is expected to condensate, one must also consider the contribution of another strongly-bound molecule, SiS (E B (SiS) = 6.46 eV), so that the first critical carbon abundance should be redefined as ε crit,1 C = ε O − ε Si + ε S . Since this study deals with the gas chemistry for log(T ) ≥ 3.2 (i.e.…”
Section: Molecular Chemistry: the Key Rôle Of The C/o Ratiomentioning
confidence: 99%
“…However our identification results seem to show that some S stars have CS and HCN absorption features. Ferrarotti & Gail (2002) found that a dramatic change of gas composition occurs in the condensation zone of circumstellar shells with lower temperatures (e.g., T < 1200 K) at a critical carbon abundance of ε C,crit = ε O −ε Si +ε S (=0.975ε O ;…”
Section: Molecular Absorption Featuresmentioning
confidence: 99%
“…here ε x means the abundance of x element) (Ferrarotti & Gail 2002). When the carbon abundance is less than ε C,crit , the gas composition is almost dominated by O-rich molecules, while when the carbon abundance is more than ε C,crit the gas composition is almost dominated by C-rich molecules.…”
Section: Molecular Absorption Featuresmentioning
confidence: 99%
See 1 more Smart Citation